Development of Membrane Electrodes for the Specific Determination of Moexipril Hydrochloride in Dosage Forms and Biological Fluids - Belal,F. (2009)
Three polyvinylchloride (PVC) membrane sensors for the determination of moexipril hydrochloride were prepared and characterized. The sensors are based on the use of the ion association complexes of moexipril cation with either ammonium reineckate (sensor 1) or tetraphenyl borate (sensor 2) or phosphotungistic acid (sensor 3) counter anions as ion exchange sites in the PVC matrix. The performance characteristics of these sensors were evaluated according to IUPAC recommendations, which reveal a fast, stable and linear response for moexipril over the concentration range of 10-6 to 10-2 M for the three sensors with cationic slopes of 29.1, 30.1 and 30.2 mV per concentration decade for the three sensors, respectively. The direct potentiometric determination of moexipril hydrochloride using the proposed sensors gave recoveries % of 99.64 ± 0.34, 99.34 ± 0.56 and 99.68 ± 0.42 for the three sensors, respectively. The sensors were used for determination of moexipril hydrochloride in pharmaceutical formulations and in plasma. Validation of the method shows suitability of the proposed sensors for use in quality control assessment of moexipril hydrochloride. The obtained results were in a good agreement with those obtained using the reported spectrophotometric method.